1998
DOI: 10.1590/s0102-05361998160205
|View full text |Cite
|
Sign up to set email alerts
|

Metodologia para avaliação da resistência de péletes

Abstract: A rigidez da camada de peletização depende da proporção de cimentante na sua constituição. Os péletes devem ser suficientemente rígidos para manterem a sua integridade física durante a classifica ção, no transporte, no manuseio ou na semeadura mecanizada. En tretanto, deve-se utilizar o mínimo de cimentante (adesivo), pois estes são geralmente produtos visguentos e a viscosidade da solução retida nos poros da camada de peletização, após a irrigação, afeta a drenagem da água e consequentemente a troca gasosa en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…The zinc sulphate has bigger, heavier particles, while the dolomite lime and the charcoal both have finer textures; boric acid sits in the middle. During the coating process materials of finer granulometry should be preferred in the layers closer to the nucleus, so an enhancement of the seed's contact surface and weight is assured (Silva and Nakagawa, 1998). This way, it is believed that the methodology utilized in this work favoured the adherence of zinc sulphate, which was not capable of keeping the surface of the layers even, by virtue of its crystalized shape, thus reducing the adhesiveness of the other materials (Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…The zinc sulphate has bigger, heavier particles, while the dolomite lime and the charcoal both have finer textures; boric acid sits in the middle. During the coating process materials of finer granulometry should be preferred in the layers closer to the nucleus, so an enhancement of the seed's contact surface and weight is assured (Silva and Nakagawa, 1998). This way, it is believed that the methodology utilized in this work favoured the adherence of zinc sulphate, which was not capable of keeping the surface of the layers even, by virtue of its crystalized shape, thus reducing the adhesiveness of the other materials (Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…In the TR4 this effect is noticeable, although they are statistically equal to control, the coated seeds obtained higher unevenness due to the barrier of the coating. According to Silva & Nakagawa (1998), this barrier imposed by the covering hinders the diffusion of gases and waters between the external environment and the seed.…”
Section: Resultsmentioning
confidence: 99%
“…Oliveira et al (2003) working with sand and limestone found a decrease in germination percentages of sweet pepper seeds. This delay in germination is a recurring problem in several studies (Silva & Nakagawa, 1998;Tunes et al, 2012;Caldeira et al 2016;Acha et al, 2016;Sousa et al, 2016;Silva et al., 2017;Xavier & Vieira, 2018;Acha et al, 2018). However, in spite of this delay, studies indicate that the process of coating seeds is a great alternative for maintaining their physiological characteristics (Medeiros et al 2004;Brites et al, 2011;Sousa et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Em complementação aos estudos anteriores, os mesmos autores em outro trabalho (Silva & Nakagawa, 1998c) verificaram a resistência dos péletes produzidos, pois estes devem ser suficientemente rígidos para manterem a sua integridade física durante a classificação, transporte, manuseio ou na semeadura mecanizada, sendo então necessário avaliar a sua resistência para que se possa utilizar a menor concentração possível de cimentantes, sem afetar a qualidade final do produto.…”
Section: Resultados De Estudos De Avaliação Do Processo Materiais E unclassified
“…Como resultados deste estudo (Silva & Nakagawa, 1998c) obteve-se que os péletes confeccionados com areia mais bentonita apresentaram os menores índices de resistência, enquanto que aqueles que receberam acabamento com calcário mais cola à base de acetato de polivinila (PVA), apresentaram resistência intermediária e aqueles confeccionados com cola PVA como único cimentante, apresentaram os maiores índices.…”
Section: Resultados De Estudos De Avaliação Do Processo Materiais E unclassified